Reconstructing Criminal Law Policy on Homicide Through Preventive Governance, Digital Forensic Investigation, Victimological Protection, and Restorative Criminal Justice Approaches - Sandra Fameyla (Asosiasi Dosen Muda Indonesia, 2026)
Homicide remains one of the most serious criminal offenses threatening social stability, human security, public order, and legal certainty within modern societies. The increasing complexity of homicide cases influenced by technological advancement, socio-economic inequality, organized crime, domestic violence, cyber-related criminal behavior, psychological disorders, and transnational criminal networks has significantly transformed contemporary criminal justice challenges. Conventional punitive approaches frequently prove insufficient in addressing the multidimensional causes and consequences of homicide because criminal acts of murder involve not only legal violations but also social, psychological, economic, cultural, and institutional dimensions. Consequently, modern criminal law governance increasingly emphasizes preventive strategies, digital forensic investigation systems, victimological protection, and restorative justice approaches within homicide prevention and criminal justice frameworks. This study aims to analyze the reconstruction of criminal law policy on homicide through preventive governance, digital forensic investigation, victimological protection, and restorative criminal justice approaches. The study employs a systematic literature review method by critically examining peer-reviewed international and national journal articles published between 2015 and 2026. The analysis integrates thematic analysis, comparative analysis, and narrative synthesis to identify governance patterns, institutional challenges, legal developments, criminological factors, and policy implications regarding homicide prevention and criminal justice systems.